Support to small and medium enterprises – business incubators in Slovakia - Kašjaková, Ol'ga (Journal of Business Economics and Management, 2004)
In both developed and developing economies, policies supporting small and medium enterprises are widely promoted as their role for economic and social development is universally recognised. Support programs range from technical assistance to tax incentives, from direct supply of capital to regulatory provisions, training, support to innovation and other types of incentives. One of the mechanisms employed to nurture small firms for more than two decades is “business incubation”.First Published Online: 14 Oct 2010